Analysis of Indonesian Government Financial Statements for the Period 2004-2023 - Friska Nurlita Lusiarini; Triyono Triyono; Zulfikar Zulfikar (Penerbit Goodwood, 2026)
Purpose: The purpose of this study was to describe the differences in the level of liquidity ratios, solvency, and Debt Service Ratio of central government finances for the period 2004-2013 with the period 2014-2023 as well as differences in the level of revenue effectiveness ratios, spending efficiency ratios, revenue growth rate ratios, spending growth rate ratios, and their harmony ratios Methodology/approach: The method used is descriptive quantitative with non-parametric test data analysis techniques Man Whithney-U model using the SPSS version 30 program. Results/findings: The results showed that the difference in liquidity ratios in the government period 2004-2013 with the period 2014-2023 which means the hypothesis is accepted. As for the solvency ratio, there is a better difference, which means the hypothesis is accepted. Meanwhile, in the 2014-2023 period, although there was considerable tax reform, the challenges in achieving revenue targets were also greater due to an increase in state spending as a result of the COVID-19 pandemic. So it is stated that the hypothesis of measuring government performance through the revenue effectiveness ratio is rejected. Then in the efficiency ratio, there is no statistically superior period in terms of the use of the state budget to achieve development goals, which means that the hypothesis is rejected. Limitations: This research is limited to measuring performance from a financial perspective contained in the Central Government Financial Statements (LKPP) for fiscal years 2004 to 2023. Contribution: This research can help the government in understanding the effectiveness of budget management in three leadership periods, so that it can be used as an evaluation material to improve financial management in the future.